Investigation of Secondary School Students' Perceptions of Leisure Boredom in the Distance Education Process - Meltem CEYLAN GENCİGÖR; Sinan AKIN; Ceren GÜMÜŞGÜL (ümit doğan üstün, 2022)
The purpose of this study was to investigate secondary school students' perceptions of leisure boredom in the distant education process according to variety of demographic factors. The study was designed as a quantitative cross-sectional study. The study sample was consisted of 214 secondary school students from Tavşanlı district of Kütahya province, who were chosen using the appropriate sampling method and willingly participated in the survey. The personal information form created by the researchers and Leisure Boredom Scale adopted into Turkish by Kara, Gürbüz, and Öncü (2014) was used as the data gathering tools. The data were analyzed using the SPSS 20 package program using independent samples t test and one way Anova. According to analyzed results, although there was no significant difference in the "satisfaction" sub-dimension of the participants' scores according to gender and class variable (p>0.05), there was a significant difference in the "boring" sub-dimension (p<0.05). Besides, while there was a significant difference in the "satisfaction" sub-dimension (p<0.05), there was no significant difference in the "boring" sub-dimension (p>0.05), according to the participants with and without a student club membership, and the time spent on the Internet. It was observed that the participants who had difficulty in evaluating the leisure time had differences in both sub-dimensions of satisfaction and boredom (p<0.05).